Critical magnetic behavior of the half Heusler alloy RhCrSi: Monte Carlo study. Issue 1 (4th May 2022) - Idrissi, S.; Ziti, S.; Labrim, H.; Bahmad, L.
Abstract: In this paper, we study the critical magnetic properties of the Half Heusler alloy RhCrSi, using Monte Carlo simulations (MCS) under the Metropolis algorithm. In fact, to study this alloy, we apply an Ising model using the MCS simulations, we concentrate only on the magnetic atoms: Rh and Cr. For this purpose, these magnetic atoms are modeled by the spin moments S = 5/2 for Rh atoms and σ = 2 for Cr atoms, respectively. In addition, we discuss the ground state phase diagrams in different planes corresponding to different physical parameters. On the other hand, for non-null temperature values, we perform the Monte Carlo simulations (MCS) to study the critical behavior of the compound RhCrSi, in the Ising approximation. Indeed, we present a detailed discussion of the obtained results for the magnetizations as a function of the temperature, the crystal field and the exchange coupling interactions. Additionally, we give the reliance of the basic temperature as an element of precious crystal field when fixing the exchange coupling interactions. To finish this work, we built up and examined the magnetic hysteresis cycles and the relating coercive fields as a part of the external magnetic field.